The importance of the press conference in organizing and conducting public events - Meylieva Gulnoza Minggirovna (Peerian Journals Publishing, 2023)
This article explores the significance of press conferences in organizing and conducting public events. It discusses the benefits and drawbacks of holding press conferences, the role of press conferences in crisis management, and best practices for conducting effective press conferences. The article highlights the importance of press conferences in disseminating accurate and up-to-date information, clarifying misunderstandings, and generating media coverage for events. By following best practices, such as preparing key messages, selecting appropriate spokespeople, and providing adequate media access, organizers can conduct successful press conferences that enhance their organization's credibility and build strong relationships with the media.
Keywords: press conference; mass event; communication